Radio-Based Cyber-Attacks Against Pacemakers: Assessing Their Chance of Success Under Real Conditions - Ngamboé, Mikaëla; Fernandez, José M.; Dyrda, Katia (Cardiology and Cardiovascular Medicine, 2021)
Proofs of concept have shown that certain models of pacemakers are vulnerable to radio-based cyber-attacks. However, to estimate an attack’s risk of occurrence, it is not enough to prove its feasibility. It is also necessary to evaluate the attack’s chances of success under real conditions. In this study, we evaluate the probability of occurrence of radio-based cyber-attacks against pacemakers. We performed some attacks and documented the difficulties encountered along the way. We then analyzed the effect that these difficulties would have on the outcome of the attacks in real life circumstances. The results of the experiments reveal that the probability of these attacks being conducted in real life is low because of the time and space requirements that are required for their success.